Dexamethasone or prednisolone for asthma exacerbations in children: a cost-effectiveness analysis (2020)
Objectives Although a short course (ie, 3 to 5 days) of orally administered prednisolone is a common and widely accepted practice among clinicians for administering systemic corticosteroids in pediatric acute asthma, oral dexamethasone for 1 to 2 days is an attractive alternative to prednisolone due to its better palatability and compliance. However, a cost‐effectiveness analysis regarding the use of dexamethasone compared to prednisolone is not sufficient, especially in lower‐ and middle‐income countries. The objective of this study was to analyze the cost‐effectiveness of prednisolone vs oral dexamethasone for treating pediatric asthma exacerbations. Methods Using a decision‐analysis model, we analyzed the cost‐effectiveness of prednisolone vs oral dexamethasone for treating acute pediatric asthma. Effectiveness parameters were derived from a systematic review of the published literature. Data for costs were acquired from hospital accounts and from an official national database, the national manual of drug prices in Colombia. The study was carried out from a Colombian third‐party payer perspective. The principal outcome of the model was the avoidance of hospitalization. Results The base‐case analysis showed that compared to dexamethasone, administering prednisolone was associated with lower overall treatment costs (US$93.97 vs US$104.91 mean cost per patient) without a significant difference in the probability of hospitalization avoided (.9108 vs .9108). Conclusions The present study shows that in Colombia, a middle‐income country, compared with oral dexamethasone, the use of prednisolone for treating acute pediatric asthma is cost‐effective, yielding a similar probability of hospitalization at lesser overall costs.